ANALYSIS OF THE AVAILABILITY AND IDENTIFICATION OF PUBLIC GREEN OPEN SPACES IN GKU 1 AND GKU 2 AT INSTITUT TEKNOLOGI SUMATERA CAMPUS - Amanda, Zulvita; Fadillah, Rayhan; Ali, Muhammad Saddam (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
Institut Teknologi Sumatera (ITERA) is a higher education institution located in the village of Way Huwi, South Lampung Regency. It was established to fulfill the educational needs centered on the island of Suamtera. ITERA campus was formerly a green area used for rubber plantations and forests which underwent transformation due to the demand for academic buildings. This transformations is ecidenced by the construction of the General Lecture Building (GKU) and Engineering Laboratory Building (Labtek) 1-4. This reserarch focuses on GKU 1 and 2, which serve as the central academic hubs for three faculties of ITERA. The aim is to identify issues related to the availability of public green open spaces in each building. Both GKU building have the potential to function as communal zones that can be utilized for discussions, relaxation, and studying due to their distinct characteristics in terms of green space forms and types. The research methodology employs both quantitative and qualitative methods, such as parameters of Responsive Environments, The Likert Scale, and interviews related to the questionnaire, with the primary target audience being ITERA’s students. The research results highlight various shortcomings and advantages in each GKU building. Recommendarions for improvemenr are expected to refine the research outcomes for ITERA.